2022
DOI: 10.3390/s22218249
|View full text |Cite
|
Sign up to set email alerts
|

User Experience during an Immersive Virtual Reality-Based Cognitive Task: A Comparison between Estonian and Italian Older Adults with MCI

Abstract: Mild cognitive impairment (MCI) is an early stage of cognitive abilities loss and puts older adults at higher risk of developing dementia. Virtual reality (VR) could represent a tool for the early assessment of this pathological condition and for administering cognitive training. This work presents a study evaluating the acceptance and the user experience of an immersive VR application representing a supermarket. As the same application had already been assessed in Italy, we aimed to perform the same study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Recent usability studies have shown that IVR is rated as an acceptable, usable, and tolerable system for cognitive training by older people with MCI. Nevertheless, cybersickness could be one of the factors that might affect the acceptance and ease of use of an IVR system in MCI [22]. Cybersickness can include a series of symptoms arising during the experience in IVR, which may include nausea, vision discomfort, headache, dizziness, and disorientation [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent usability studies have shown that IVR is rated as an acceptable, usable, and tolerable system for cognitive training by older people with MCI. Nevertheless, cybersickness could be one of the factors that might affect the acceptance and ease of use of an IVR system in MCI [22]. Cybersickness can include a series of symptoms arising during the experience in IVR, which may include nausea, vision discomfort, headache, dizziness, and disorientation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, cybersickness could be one of the factors that might affect the acceptance and ease of use of an IVR system in MCI [22]. Cybersickness can include a series of symptoms arising during the experience in IVR, which may include nausea, vision discomfort, headache, dizziness, and disorientation [22]. A usability study has also been proven to identify those elements that could prevent the use of the technology [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Funny and serious games, including life skills, were implemented. Mondellini et al ( 2022 ) exposed 15 older adults diagnosed with MCI to a virtual supermarket. The participants were requested to do the shopping, picking the item presented in a list and putting them in a cart.…”
Section: Discussionmentioning
confidence: 99%